Pengukuran PDRB Hijau Subsektor Pertambangan Batubara di Provinsi Kalimantan Selatan - Ariana, Novia; Sopiana, Yunita (PPJP Universitas Lambung Mangkurat, 2023)
This study aimed to determine the value of natural resource depletion and land degradation and the importance of green GRDP in the coal mining sub-sector of South Kalimantan Province by using a green GRDP calculation approach. This research is descriptive research with a quantitative approach. The data type used is secondary data in the form of a time series from 2016 to 2020. The results of the analysis of this study indicate that the value of coal resource depletion has fluctuated, with the highest value acquisition occurring in 2018, which was Rp73,78 billion. Meanwhile, the degradation value of coal mining land is tremendous, with the highest acquisition value of Rp—66.88 trillion in 2018. The Green GRDP value of the Coal Mining Subsector shows a negative value. This means the value of depreciation or reduction and environmental damage from coal mining activities is greater than the added value generated from the coal mining sub-sector.